Equilibrium States Under Constraint in a Variational Problem on a Surface - Vyridis, Panayotis; Ndjatchi, M.K. Christophe; Flores, Fernando García; Urbina, Julio César Flores (Discontinuity, Nonlinearity, and Complexity, 2026)
We study the equilibrium states for an energy functional with a parametric force field on a region of a surface under a constraint of geometrical character. We use an improved method, based in Skrypnik’s variational theories [10]. In local coordinates, equilibrium points satisfy an elliptic boundary value problem. This model can be described as the deformation of the elastic medium and membranes.